DAMPAK LIBERALISASI PERDAGANGAN GLOBAL DAN PERUBAHAN KONDISI EKONOMI-POLITIK DOMESTIK TERHADAP DINAMIKA PERDAGANGAN LUAR NEGERI KELOMPOK KOMODITAS BERBASIS PERTANIAN DI INDONESIA - BAMBANG RAHMANTO (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Impact of global trade liberalism and domestically of economic and politicalchange to the dynamism of foreign trade of Indonesian agriculture product. Theimplementation of global trade liberalism as a result of the agreement of agricultureWTO-1994 is accused to provide more benefit to developed countries than developingcountries. Phenomena of economic crisis and implementation of autonomy process is alsoassumed to be strongly influence to create the dynamism of foreign trade of Indonesianagriculture product. This study is conducted to identify the impact of those phenomena.The outcome of the study identifies that aggregately the role of agriculture commoditygroup is decreased in both the contribution surplus of Indonesian foreign trade and itsgrowth during global trade liberalism period. Meanwhile, the result of desegregationanalysis by regression method indicate that global trade liberalism has significance effectin increasingly deficit trade of commodity group of cereal, sugar, milk, live animal, andresidues product of milling industry. Otherwise, affect significantly in increasing surplusto commodity group that related to fishery, estate and preparation products. Condition ofcrisis economic tend to decrease of deficit of some commodity group that was everdeficit, except for commodity group of sugar. For surpluses commodity group, the effectare varied. During implementation of autonomy process indicate that deficit ofcommodity group of sugar and cereal was decreases as a result of governmentintervention in controlling import surge of sugar and rice.